2022
DOI: 10.1002/mc.23420
|View full text |Cite
|
Sign up to set email alerts
|

HIF‐1α‐regulated stanniocalcin‐1 mediates gemcitabine resistance in pancreatic ductal adenocarcinoma via PI3K/AKT signaling pathway

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has a poor response to the first‐line chemotherapy drug gemcitabine. We previously identified stanniocalcin‐1 as a gemcitabine‐resistant‐related gene, but its specific role and function in pancreatic cancer remain unclear. RT‐qPCR and Western blot were used to evaluate differential protein and mRNA expressions. The biological functions of genes were determined using proliferation and drug‐resistance experiments. Subcutaneous tumorigenesis experiment was performed on nude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The elevated expression of STC2 in cervical cancer cells has been reported to significantly increase cisplatin resistance 38 . Both in vivo and in vitro results indicated that STC1 mediated gemcitabine resistance in pancreatic ductal adenocarcinoma 39 . Our previous study showed that sunitinib treatments reduced the expression of STC2 both mRNA and protein levels, which could reduce sunitinib resistance of Caki-1 cells 30 .…”
Section: Discussionmentioning
confidence: 98%
“…The elevated expression of STC2 in cervical cancer cells has been reported to significantly increase cisplatin resistance 38 . Both in vivo and in vitro results indicated that STC1 mediated gemcitabine resistance in pancreatic ductal adenocarcinoma 39 . Our previous study showed that sunitinib treatments reduced the expression of STC2 both mRNA and protein levels, which could reduce sunitinib resistance of Caki-1 cells 30 .…”
Section: Discussionmentioning
confidence: 98%
“…The GEM resistance-associated gene stanniocalcin-1 (STC1) is related to the prognosis of patients with adjuvant GEM chemotherapy after surgery. Recently, cell and animal models have further validated that STC1 mediates chemoresistance to PC under the action of the HIF-1α/STC1/PI3K-AKT axis ( Zhao et al, 2022 ). Long noncoding RNA antisense RNA1 of HIF1α (lncRNA HIF-1α-AS1) also promotes GEM resistance in PC cells through the AKT/YB1/HIF-1α pathway ( Xu F. et al, 2021 ).…”
Section: Alterations In Glucose Metabolismmentioning
confidence: 99%
“…The PTEN/PI3K/AKT pathway is important in regulating gemcitabine chemosensitivity of pancreatic cancer [36][37][38][39]. Therefore, we aimed to investigate whether FTO and NEDD4 affect gemcitabine chemosensitivity by modulating the PTEN/PI3K/AKT pathway.…”
Section: Nedd4 Regulated By Fto and Ythdf2 Affects The Chemosensitivi...mentioning
confidence: 99%